THE UEFA INJURY STUDY: 11-YEAR DATA CONCERNING 346 MCL INJURIES IN PROFESSIONAL FOOTBALL. Issue 7 (11th March 2014) - Lundblad, M; Waldén, M; Magnusson, H; Hägglund, M; Karlsson, J; Ekstrand, J
Abstract : Background: Medial collateral ligament (MCL) injury of the knee is scarcely investigated in football. Objective: To investigate the rate and circumstances of MCL injuries and their development over the past decade. Design: Prospective cohort study, in which 27 professional football teams were followed between 2001/02 and 2011/12. Individual player exposure and time loss injuries were recorded. Setting: Highest leagues in Europe. Participants: 1 743 male professional players. Risk factor assessment: Seasonal trend, expressed as the average annual percentage of change, was analysed using linear regression with log-transformed injury rates as the dependent variable. A 2-year moving average approach, by summarising two consecutive seasons, was also used to smooth out large seasonal variations. Injury circumstances such as player contact and foul play was also studied. Main outcome measurements: Injury rate was defined as the number of injuries per 1000 player hours. Results: 346 MCL injuries occurred during the study period, being the most common knee injury constituting 4% of all injuries. The MCL injury rate was 0.33 per 1000 hours, and a time trend analysis indicated a significant average annual decrease of approximately seven per-cent over the study period (P=.023). Almost 70% of all MCL injuries were contact-related, and no difference in lay-off times between contact (median=16, Q1=8, Q3=29) and non-contact (median=16, Q1=7, Q3=30) injuries was detected (P=.741). A higher percentage of foul play injuries were found in MCL contact injuries compared with other contact injuries during match play (24% vs. 18%, P=.015). Conclusion: MCL injury is still the most frequent knee injury in professional football, but the rate has decreased significantly during the 11-year study period. MCL injuries are commonly caused by contact situations and foul play.